Utility and democracy in political campaign advertising: toward a rule-utilitarian ethic for political marketing and the ethics of meddling in the other party's primary - Reed, Joel (Journal of business ethics, 2026)
Political advertising ethics has long been dominated by an adherence to the norms of democratic idealism or the highly situational ethics of act utilitarianism. This article proposes an alternative system of political advertising ethics grounded in Brandt’s ideal moral code theory, a form of rules-based utilitarianism. To illustrate the relative advantage of rule utilitarianism, the author investigates the ethics of advertising campaigns aimed at intervening in an opposing party’s primary. The past decade has seen a dramatic resurgence in Democratic and Republican candidates in the United States meddling in the opposing party’s primary through advertising campaigns designed to exploit tensions between electability and viability within the political outgroup. The author critiques the common act-utilitarian defenses of interparty-intraparty intervention and proposes a rule-utilitarian alternative that prioritizes the preservation of democratic norms over individual election outcomes.